2015
DOI: 10.3923/ajsr.2015.237.244
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a MEMS 3D Micro-transformer for Low Frequency Applications

Abstract: This study presents the fabrication of a 3D micro-transformer using MEMS technology in 10-600 kHz frequency range. The fabrication processes is developed for high-performance and low-cost realization with respect to planner design. The coil winding and the magnetic cores were fabricated by electro-deposition using copper and Ni/Fe Permalloy materials, respectively. In step-up configuration, the micro-transformer achieved 73.75% efficiency. The inductance achieved was 90 and 164 µH for primary and secondary coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…For the coplanar devices with racetrack geometry, k values up to 0.93 have been reported by Wang et al [71], [78], but inductance values were relatively low (just a few dozens of nH). Ahmed et al were able to build a device with high inductance values (L1 = 90 µH and L2 = 164 µH at 1 kHz) in a footprint area of 2.56×1.24 mm 2 using a solenoidracetrack with a Ni-Fe Permalloy core [83]. The authors also reported a 73.75% efficiency at 50 kHz using a 1 kΩ load resistor, which is a good result for a microtransformer.…”
Section: Racetrackmentioning
confidence: 98%
See 1 more Smart Citation
“…For the coplanar devices with racetrack geometry, k values up to 0.93 have been reported by Wang et al [71], [78], but inductance values were relatively low (just a few dozens of nH). Ahmed et al were able to build a device with high inductance values (L1 = 90 µH and L2 = 164 µH at 1 kHz) in a footprint area of 2.56×1.24 mm 2 using a solenoidracetrack with a Ni-Fe Permalloy core [83]. The authors also reported a 73.75% efficiency at 50 kHz using a 1 kΩ load resistor, which is a good result for a microtransformer.…”
Section: Racetrackmentioning
confidence: 98%
“…Regarding the performances, only a few authors determined the k and Q parameters for microtransformers using the racetrack geometry. Some articles reported coupling coefficients for racetrack solenoid devices to be in the 0.5-0.9 range, but in most cases custom-made core materials were used, instead of those commercially available [43], [47], [61], [70], [83]. For the coplanar devices with racetrack geometry, k values up to 0.93 have been reported by Wang et al [71], [78], but inductance values were relatively low (just a few dozens of nH).…”
Section: Racetrackmentioning
confidence: 99%
“…Considering this issue, there have been attempts to fabricate on-chip transformers with integrated magnetic cores [86,87,88,89,90]. In one study, a micro-assembly system with robotic microgripper was introduced to fabricate out-of-plane 3D microstructures [86].…”
Section: Design Strategies and Mems Process Flows To Improve On-chmentioning
confidence: 99%
“…In such a fabrication strategy, the transformer windings consist of two layers of conductors between which a magnetic core is sandwiched, and vias are used to connect the top and bottom conductor layers [87] (Figure 7b). With this approach, an on-chip transformer with a magnetic core of 7-µm-thick patterned Permalloy (Ni-Fe) was fabricated, and characterized to exhibit inductance values of 90 µH and 164 µH for primary (10 turns) and secondary windings (18 turns) respectively, for frequencies below 600 kHz [88]. Similar fabrication approach with improved transformer design to realize monolithic transformers with Ni-Fe-W core was also reported where high frequency transformer operation reaching 70 MHz was achieved [87] (Figure 7c).…”
Section: Design Strategies and Mems Process Flows To Improve On-chmentioning
confidence: 99%
“…Electroplated permalloy (Ni81Fe19) has been widely used for magnetic flux concentrators [1], [2] and micro transformers [3]- [7] due to their high magnetic permeability and small coercivity.…”
Section: Introductionmentioning
confidence: 99%